Pengembangan Sistem Aplikasi Tokokue Berbasis Web dengan PHP - Dwicky Oktavian Widodo; Zulfikar Alwi; Atep Taufik Rianto; Roby Chairul Anam Kurniawan; Teti Desyani; Yulianti Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Tokokue is one of the stores that is engaged in processing and selling food (Bread and Cake), the information system at Tokokue is currently a conventional system or buyers must come directly to the store to see and choose the cake or bread they want, with the system making buyers or consumers find it difficult to choose the desired product because they have to come directly to the store and take up consumers' time. Based on these problems, an information system was designed and developed at Tokokue, which was built using the PHP programming language and using MySQL, including using the Use Case Diagram and Activity Diagram models. The system that will be developed with reference to make it easier for consumers to use and improve sales services. The results of using this web-based application, online sales make Tokokue sales increase, with the development of a web-based sales system, and the features in this application make it easier for buyers or consumers from various cities to view and choose products with an easier payment process. namely by means of transfer. With a good product data development or management system, it will support the performance of the system.